2022
DOI: 10.3389/fvets.2022.892709
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Supplying Ruminally Protected Lysine and Methionine to Periparturient Dairy Cows on the Efficiency of Subsequent Lactation

Abstract: The objective of this study was to evaluate the effects of supplying ruminally protected Lys (RPL) and ruminally protected Met (RPM) to transition cows' diets on the efficiency of subsequent lactation. A total of 120 prepartum Holstein cows were assigned into four treatments blocked by the anticipated calving date, previous lactation milk yield, number of lactations, and body condition score and fed either RPL, RPM, or the combination (RPML) or control diet (CON) throughout the transition period (3 weeks befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
1
1
0
2
Order By: Relevance
“…The results of this investigation show consistent outcomes in favor of the LYS × MET group when compared to the trial of the spring season in which only the LYS group saw positive effects in primiparous cows, and the MET group did the same only in multiparous cows [14]. As a result, this investigation reports similar results to studies carried out in animals managed under complete confinement, where the supplementation of both AAs could reach a ratio of 2.70, which has shown positive effects on milk production and/or its protein and fat content [10,27,28]. It is suggested that the supplementation of both AAs during the fall season benefits the levels of fat and protein for the reason that pasture consumption is limited to only 5 kg of DM per cow daily, receiving a higher proportion of a PMR, which is greatly resemblant to a conventional confined herd fed a 100% TMR.…”
Section: Discussionsupporting
confidence: 67%
“…The results of this investigation show consistent outcomes in favor of the LYS × MET group when compared to the trial of the spring season in which only the LYS group saw positive effects in primiparous cows, and the MET group did the same only in multiparous cows [14]. As a result, this investigation reports similar results to studies carried out in animals managed under complete confinement, where the supplementation of both AAs could reach a ratio of 2.70, which has shown positive effects on milk production and/or its protein and fat content [10,27,28]. It is suggested that the supplementation of both AAs during the fall season benefits the levels of fat and protein for the reason that pasture consumption is limited to only 5 kg of DM per cow daily, receiving a higher proportion of a PMR, which is greatly resemblant to a conventional confined herd fed a 100% TMR.…”
Section: Discussionsupporting
confidence: 67%
“…Ві-домо, що інфекційні хвороби слизових оболонок у дорослих тварин негативно впливають на процес запліднення і перебіг вагітності (аборти). Крім того, на відтворну функцію корів впливає продуктивність, відомо, що підвищення молочної продуктивності на 500 кг зумовлює зниження заплідненості (Elsaadawy et al, 2022). Результати досліджень подані у таблиці 3.…”
Section: рис 1 структура гінекологічної патології в господарствахunclassified
“…Досліджено залежність розладів роботи яєчників при підвищенні продуктивності у корів. При цьому встановлено зниження заплідненості на 11,8 % при підвищенні продуктивності на 500 літрів за лактацію, про що зауважують і інші дослідження (Elsaadawy et al, 2022).…”
Section: обговоренняunclassified
“…RPM, in synergy with other amino acids, has similarly shown positive effects on the production performance and the metabolic aspects of dairy cattle. Importantly, a study has documented that milk yield [12], as well as energy-corrected milk (ECM), milk fat, protein, and lactose percentage levels, exhibited enhancements in cows supplemented with RPM and lysine compared to the control group [49,50]. Furthermore, the study ascertained that supplementation with RPM and RP-lys preserved the post-calving body condition score (BCS), enhanced DMI, and reduced the blood concentrations of BHBA [49,50].…”
Section: Introductionmentioning
confidence: 99%